SAT0463 Secukinumab provides sustained reduction in fatigue in patients with active psoriatic arthritis through 3 years: long-term data from the future 1 and future 2 studies. (15th June 2017) - Gossec, L; Kvien, TK; Conaghan, PG; Østergaard, M; Gladman, D; Mease, P; Rasouliyan, L; Pricop, L; Gaillez, C; Jugl, S
Abstract : Background: Fatigue, a common symptom in patients (pts) with PsA, can negatively impact HRQoL and social functioning. Secukinumab (SEC), a fully human anti–IL-17A mAb, rapidly improved signs and symptoms, physical functioning, HRQoL, and fatigue in pts with PsA. 1, 2 Objectives: To assess the long-term effects of SEC on fatigue in TNF inhibitor (TNF)-naïve PsA pts and those with an inadequate response or intolerance to TNF inhibitor therapy (TNF-IR). Methods: 606 and 397 pts were randomized to SEC or placebo (PBO) in FUTURE 1 (10 mg/kg IV followed by 150 or 75 mg SC) and FUTURE 2 (300, 150, or 75 mg SC), respectively. At Wk 16, PBO pts with ≤20% reduction in tender/swollen joint count (non-responders) were re-randomized to SEC 150 or 75 mg SC (FUTURE 1) and SEC 300 or 150 mg SC (FUTURE 2); responders were re-randomized at Wk 24. Pts in FUTURE 1 could enter a LTE study at Wk 104 (NCT01892436 ). Across both studies, approximately 68% of pts were TNF-naïve and 32% were TNF-IR. Fatigue was assessed at baseline (BL) and Wks 4, 8, 12, 16, 24, 52, 104, and 156 (FUTURE 1 only) using FACIT-F (higher scores = less fatigue). Fatigue response was defined by an increase in FACIT-F score of ≥4 from BL (corresponding to the MCID). Correlations between BL characteristics and improvements in fatigue were investigated using a logistical regression model. Only data with approved doses of SEC (300/150 mg) are shown. Results: FACIT-F was 27.8–28.9 and 26.6–29.2 at BL across groups in FUTURE 1 and 2, respectively. Improvements in fatigue seen with all doses of SEC vs. PBO from Wks 4–24 were sustained through 156 wks in FUTURE 1 and 104 wks in FUTURE 2 in both the overall population and subgroups stratified by prior exposure to TNF (Table). The numerically higher responses with SEC 150 vs. 300 mg in this observed analysis were as a result of a higher rate of discontinuation due to lack of efficacy with the lower dose, which inflated the response rate. In the overall population, the LS mean change (±SEM) from BL in FACIT-F was significantly greater with SEC vs. PBO at Wk 16 in both FUTURE 1 (7.25±0.72 vs. 4.07±0.76; P =0.002) and FUTURE 2 (300 mg: 5.89±0.92 vs. 1.86±0.93, P =0.002; 150 mg: 7.40±0.90 vs. 1.86±0.93, P <0.0001); improvements were sustained throughout the entire follow up in both studies (FUTURE 1 Wk 156: 6.14±0.77; FUTURE 2 Wk 104: 300 mg 7.29±1.04, 150 mg 7.02±1.06). Improvements were generally somewhat larger in TNF-naïve pts than in TNF-IR pts. Correlation analyses did not identify any BL factors that consistently predicted change in fatigue score across Wks 16, 52, and 104. Conclusions: SEC-treated PsA pts achieved rapid, sustained, and clinically meaningful improvements in fatigue for up to 156 wks, with higher responses in TNF-naïve pts. References: McInnes et al. Lancet 2015;386:1137–46. Mease et al. N Engl J Med 2015;373:1329–39. Disclosure of Interest: L. Gossec Grant/research support from: BMS, Lippy, Pfizer; Consultant for: Abbvie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Roche and UCB, T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz and UCB, P. Conaghan Consultant for: Abbvie, BMS, Lilly, Novartis, Pfizer, Roche, Speakers bureau: Abbvie, BMS, Lilly, Novartis, Pfizer, Roche, M. Østergaard Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Janssen, Merck, Novartis, Orion, Pfizer, Regeneron, Roche, UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Janssen, Merck, Novartis, Orion, Pfizer, Regeneron, Roche, UCB, D. Gladman Grant/research support from: Abbvie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Consultant for: Abbvie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, P. Mease Grant/research support from: Abbvie, Amgen, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Janssen, Merch, Novartis, Pfizer, SUN, UCB, Consultant for: Abbvie, Amgen, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Janssen, Merch, Novartis, Pfizer, SUN, UCB, Speakers bureau: Abbvie, Amgen, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Janssen, Merch, Novartis, Pfizer, SUN, UCB, L. Rasouliyan Consultant for: Novartis, L. Pricop Shareholder of: Novartis, Employee of: Novartis, C. Gaillez Shareholder of: Novartis and BMS, Employee of: Novartis, S. Jugl Shareholder of: Novartis, Employee of: Novartis